Підвищення екологічної безпеки водних об’єктів в зоні впливу звалищ твердих побутових відходів - Михайленко, Валерія Валеріївна (НТУ "ХПІ", 2015)
Робота присвячена дослідженню технологічних заходів щодо підвищення рівня екологічної безпеки водних об'єктів в зоні негативного впливу звалища твердих побутових відходів м. Маріуполя. Розроблені комплексні заходи щодо перешкоджання потрапляння забрудненого фільтрату в підземні води та ріку Кальміус. Визначено оптимальні умови процесу анаеробного зброджування за яких ефективність очищення максимальна. Доведено ефективність застосування методу осадження для видалення заліза з фільтрату звалища ТПВ та шаруватих подвійних гідроксидів для сорбції фенолів. Визначено оптимальний склад нейтралізуючої суміші.

This article is about the development of technology to protection of water sources from dumps drains. To eliminate the negative impact of dump the scheme complex recycling and purification sump sewage was proposed. The method of anaerobic digestion was proposed for sewage treatment. The dependence of the fermentation process on the temperature was defined. We founded that the optimum temperature of the process is 54-55ºC. It is proved that the final content of helminths and enterobacterias at a given temperature least. It is established that the use of continuous operation of organization of the process most effectively. The method of sedimentation with pH increase for drains treatment was proposed. This leads to the binding of the precipitate of hydroxides. As neutralizing mixture are using a calcium hydroxide and metallurgical slag. The sorbents–double layered hydroxides are proposed for phenols remove. The processes of precipitation was investigated. The parameters of safe neutralization process, prevention of ingress of contaminants into the air were studied. The Scientific novelty of the got results is the study of chemical and biological contamination of dumps drains in Mariupol city. The development of theoretical substantiation and experimental verification process of anaerobic digestion drains, which leaked to the surface near the body dump of biological contamination. The parameters that provide the greatest degree of purification were determinated. Scientifically grounded and calculated parameters of cleaning liquid phase storage of phenol using sorbents-layered double hydroxides of iron ions and using calcium oxide.
The increase of ecological protection of water bodies in the area of dumps impact
Keywords: навколишнє середовище; фільтрат звалищ; анаеробне зброджування; шаруваті подвійні гідроксиди; environmental protection; dump; drains; layer double hydroxide; anaerobic digestion